FORMATION OF A COMPREHENSIVE HARMONIOUS PERSONALITY-THE MAIN GOAL OF NATIONAL EDUCATION (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article analyzes the approaches to the upbringing of the perfect generation in the social life of our society at a new stage of development, as well as the issues of the role of the idea of interethnic harmony in this process. Approaches from various sources were analyzed by the author and final conclusions were drawn.